RISK FACTORS OF MUTATION NUCLEOTIDE OLIGOMERAZATION DOMAIN 2 GENE TO CHRONIC PERIODONTITIS: MUTASI GEN NUCLEOTIDE OLIGOMERAZATION DOMAIN 2 (NOD2) SEBAGAI FAKTOR RISIKO TERHADAP TERJADINYA PERIODONTITIS KRONIS - Asmawati (TALENTA, 2011)
Chronic periodontitis is a chronic inflammatory disease that causes a damage of tooth supporting tissues. The incidence of chronic periodontitis disease is highly reported in Indonesia .S urvey in Java, Bali and Sulawesi reported the incidence of chronic periodontitis for 35-44 years age group was 88.67%. This disease is a major cause of tooth loss for 35 years or more age group. The results of various studies was found many chronic periodontitis diseases are common in young age, therefore the genetic role in diseases is susceptible for chronic periodontitis. The aim study was to know if the mutation of the gene Nucleotide-Binding Oligomerization Domain 2 (NOD2) is a risk factors for chronic periodontitis. Total sample was 162 subject, 81 samples with chronic periodontitis and 81 without periodontal disease as control group. The results showed that there was 12,3 % of samples that had been mutation of NOD2 gene, and in the control group only 1,2 %, and statistical l y there was a significant difference ( p=0,005). In conclusion, mutation NOD2 gen is a risk factor to chronic periodontitis.